Persistent pain associated with socioeconomic and personal factors in a Sami and Non-Sami population in Norway: an analysis of SAMINOR 2 survey data - Damsgård, Elin; Thrane, Gyrd; Fleten, Nils; Bagge, Johan; Sørlie, Tore; Anke, Audny; Broderstad, Ann Ragnhild (International Journal of Circumpolar Health, 2020)
In international studies, higher prevalence of persistent pain has been reported in indigenous populations compared to majority populations. The present study aimed to determine the prevalence of persistent pain within a Sami and a non-Sami population in northern Norway, with adjustment for the confounding factors of age, sex, marital status, education, income, mental health, smoking status and ethnic background. Using SAMINOR 2 survey data including Sami and non-Sami populations, we analysed 5,546 responses, from individuals aged 40–79 years, to questions concerning persistent pain (≥ 3 months). In total, 2,426 (43.7%) participants reported persistent pain with differences between Sami women and non-Sami women (44.1% versus 51.1%, respectively), but none between Sami men and non-Sami men (38.7% versus 38.2%, respectively). Elderly Sami women were less likely to report persistent pain than were elderly non-Sami women. In men, no ethnic differences in pain were observed according to age-group. Marital status, education levels, household income, psychological distress, and smoking status did not influence the association between ethnicity and pain. Pain severity and location did not differ between Sami and non-Sami participants. In this study, we found only minor ethnic differences in persistent pain. Similar living conditions and cultural features may explain these findings.